IMAGINING INDIA, DECOLONIZING L'INDE FRANÇAISE, c. 1947–1954*. (29th October 2015) - Unknown
Abstract: This article examines the final years of French rule in India. It questions the established narrative of the merger of the French settlements, which implied that they were always a 'natural' part of the Indian Union. It argues, on the contrary, that a full merger was only one of several possibilities for the various actors involved in the negotiations that took place between the independence of India in 1947 and the French withdrawal in 1954. Even those who supported a merger did so for different reasons, while a significant proportion opposed the merger on economic, social, and historical grounds. By examining more closely the opposing positions in the merger debate, we can locate them within the larger tensions of early post-colonial India – a new state that was struggling to define its geographical and ideological boundaries. This suggests that the decolonization of French India was not simply another chapter in French imperial decline; it was also an important example of Indian nation-building.